The Impact of XML Databases Normalization on Design and Usability of Internet Applications - El-Sofany, Hosam F.; Ghaleb, Fayed F. M.; Abou El-Seoud, Samir (International Journal of Advanced Corporate Learning (iJAC), 2010)
Database normalization is a process which eliminates redundancy, organizes data efficiently and improves data consistency. Functional, multivalued, and join dependencies (FDs, MVDs, and JDs) play fundamental roles in relational databases where they provide semantics for the data and at the same time are the foundations for database design. In this study we investigate the issue of defining functional, multivalued and join dependencies and their normal forms in XML database model. We show that, like relational databases, XML documents may contain redundant information, and this redundancy may cause update anomalies. Furthermore, such problems are caused by certain dependencies among paths in the document. Our goal is to find a way for converting an arbitrary XML Schema to a well-designed one that avoids these problems. We extend the notion of tuple for relational databases to the XML model. We show that an XML tree can be represented as a set of tree tuples. We introduce the definitions of FD, MVD, and JD and new Normal Forms of XML Schema that based on these dependencies (X-1NF, X-2NF, X-3NF, X-BCNF, X-4NF, and X-5NF). We show that our proposed normal forms are necessary and sufficient to ensure all conforming XML documents have no redundancies.